Protein Kinase A and 5′ AMP-Activated Protein Kinase Signaling Pathways Exert Opposite Effects on Induction of Autophagy in Luteal Cells - Przygrodzka, Emilia; Monaco, Corrine F.; Plewes, Michele R.; Li, Guojuan; Wood, Jennifer R.; Cupp, Andrea S.; Davis, John S. (Frontiers in Cell and Developmental Biology, 2021)
In the absence of pregnancy the ovarian corpus luteum undergoes regression, a process characterized by decreased production of progesterone and structural luteolysis involving apoptosis. Autophagy has been observed in the corpus luteum during luteal regression. Autophagy is a self-degradative process important for balancing sources of cellular energy at critical times in development and in response to nutrient stress, but it can also lead to apoptosis. Mechanistic target of rapamycin (MTOR) and 5' AMP-activated protein kinase (AMPK), key players in autophagy, are known to inhibit or activate autophagy, respectively. Here, we analyzed the signaling pathways regulating the initiation of autophagy in bovine luteal cells. In vivo studies showed increased activating phosphorylation of AMPKα (Thr172) and elevated content of LC3B, a known marker of autophagy, in luteal tissue during PGF2α-induced luteolysis. In vitro, AMPK activators (1) stimulated phosphorylation of regulatory associated protein of MTOR (RPTOR) leading to decreased activity of MTOR, (2) increased phosphorylation of Unc-51-Like Kinase 1 (ULK1) and Beclin 1 (BECN1), at sites specific for AMPK and required for autophagy initiation, (3) increased levels of LC3B, and (4) enhanced colocalization of autophagosomes with lysosomes indicating elevated autophagy. In contrast, LH/PKA signaling in luteal cells (1) reduced activation of AMPKα and phosphorylation of RPTOR, (2) elevated MTOR activity, (3) stimulated phosphorylation of ULK1 at site required for ULK1 inactivation, and (4) inhibited autophagosome formation as reflected by reduced content of LC3B-II. Pretreatment with AICAR, a pharmacological activator of AMPK, inhibited LH-mediated effects on RPTOR, ULK1 and BECN1. Our results indicate that luteotrophic signaling via LH/PKA/MTOR inhibits, while luteolytic signaling via PGF2α/Ca2+/AMPK activates key signaling pathways involved in luteal cell autophagy.